Efektivitas Psikoedukasi Sense of Community untuk Meningkatian Komitmen Anggota Komunitas Sepak Bola - Wahyudi, Iwan; Rina, Amersthia (Jurnal Psikologi, 2025)
This study examined the commitment and cohesiveness of members within the Hura-Hura FC amateur football community in Sidoarjo, Indonesia. Using a mixed-method approach that combined observation, interviews, questionnaires, and focus group discussions, the assessment identified a significant decline in member commitment and participation. Based on Meyer and Allen’s Three-Component Model of Commitment, findings showed decreases across affective, continuance, and normative dimensions, primarily caused by ineffective communication, lack of appreciation, monotonous training routines, and time constraints. To address these issues, a psychoeducational intervention titled “Building a Sense of Community and Commitment” was implemented to strengthen emotional bonds, trust, and responsibility through interactive learning, reflection, and group collaboration. The intervention improved members’ understanding of community values, communication, and motivation, though consistent behavioral change and attendance required further reinforcement. Challenges such as uneven participation and limited online engagement highlighted the need for sustainable follow-up efforts. Therefore, continuous psychoeducation, structured appreciation systems, and enhanced communication channels were recommended to ensure long-term cohesion. This study underscores that member commitment in community-based sports is shaped not only by participation structure but also by emotional attachment, recognition, and shared purpose).